2007
DOI: 10.1002/mus.20820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a CRF2R agonist and exercise on mdx and wildtype skeletal muscle

Abstract: Corticotrophin-releasing factor 2 receptor (CRF2R) agonists prevent muscle atrophy due to immobilization, denervation, and corticosteroid-induced muscle atrophy in wildtype mice. We hypothesized that a CRF2R agonist will increase skeletal muscle mass in mdx mice. Mdx (C57BL/10ScSn-Dmd(mdx)) and wildtype (C57BL/6) mice were divided into four groups: sedentary placebo, sedentary CRF2R agonist, exercised placebo, and exercised CRF2R agonist. Mice exercised on a treadmill twice weekly for 30 min (8-12 m/min, 8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
(47 reference statements)
1
17
0
1
Order By: Relevance
“…Adaptive functions of sustained GPCR signaling have been identified using chronic treatment with agonists and antagonists in humans and model organisms (9,18,43,57,63,86,91,101,115,121,154,155,197) as well as by targeted genetic approaches in mice (42,163,164). These and other studies have revealed striking myofiber hypertrophy and fiber-type transitions to faster fiber types with prolonged activation of ␤-AR signaling in particular.…”
Section: Camp In Functional Adaptation Of Skeletal Musclementioning
confidence: 99%
See 4 more Smart Citations
“…Adaptive functions of sustained GPCR signaling have been identified using chronic treatment with agonists and antagonists in humans and model organisms (9,18,43,57,63,86,91,101,115,121,154,155,197) as well as by targeted genetic approaches in mice (42,163,164). These and other studies have revealed striking myofiber hypertrophy and fiber-type transitions to faster fiber types with prolonged activation of ␤-AR signaling in particular.…”
Section: Camp In Functional Adaptation Of Skeletal Musclementioning
confidence: 99%
“…␤ 2 -AR agonists have also been shown to reduce muscle atrophy in animals with cancer cachexia (31,33,46). In addition, agonists for ␤ 2 -AR or CRF receptors improve muscle function in dystrophin-deficient mdx (86,90,103,185,192,254,256) and laminin-deficient dy/dy (94) mice. However, efficacy of ␤ 2 -AR agonists on muscle size and force generation vary with the type and dose of agonist, as well as the muscle studied.…”
Section: Camp In Functional Adaptation Of Skeletal Musclementioning
confidence: 99%
See 3 more Smart Citations